Needs analysis for critical reading e-book based on problem-based learning: Perspectives from EFL students, lecturers, and stakeholders - Jaya, Sinarman; Hamzah, Syukri; Yunita, Wisma (Indonesian Journal of Educational Development (IJED), 2025)
Indonesian higher education is placing more emphasis on developing 21st-century skills, which require EFL students to read critically, evaluate arguments, and synthesize information from various sources. However, many EFL students still struggle with critical reading due to low motivation, passive reading habits, and a lack of engaging and relevant materials. This study explored the features, content, and design elements needed to help students improve their critical reading skills using Problem-Based Learning (PBL). A mixed-methods approach was used, involving a survey of 120 EFL students from four universities in Bengkulu, Indonesia. Interviews were also conducted with 20 students, 8 English lecturers, 4 heads of English study programs, 4 alumni, 2 school principals (from junior and senior high schools), and representatives from government institutions and private companies. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic content analysis. The research instruments were validated by experts in content, evaluation, and language, followed by a small pilot study to check for clarity and reliability. The findings showed that students prioritize content relevance, clear navigation, and interactive tasks that encourage deeper engagement with texts. Lecturers emphasized the need for the e-book to align with course objectives and incorporate higher-order thinking through task-based learning. Stakeholders stressed the importance of the e-book aligning with institutional goals and supporting critical reading, thinking, collaboration, and problem-solving skills. The study’s multi-perspective approach provides a foundation for developing a relevant, engaging PBL-based e-book to enhance EFL critical reading instruction.